Handbook on Marine Environment Protection 2017
DOI: 10.1007/978-3-319-60156-4_18
|View full text |Cite
|
Sign up to set email alerts
|

Climate Change: Warming Impacts on Marine Biodiversity

Abstract: In this chapter, the effects of temperature change-as a main aspect of climate change-on marine biodiversity are assessed. Starting from a general discussion of species responses to temperature, the chapter presents how species respond to warming. These responses comprise adaptation and phenotypic plasticity as well as

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(28 citation statements)
references
References 109 publications
(119 reference statements)
0
27
0
1
Order By: Relevance
“…These phenological shifts are particularly important as they dictate the biotic and abiotic conditions to which offspring will be exposed. Consequently, larval survival could be impacted due to mismatch with prey (plankton) abundance or proper size spectrum, for example due to delayed spawning time, inducing starvation or slower growth (Asch et al ., 2019; Farmer et al ., 2015; Hillebrand et al ., 2018; Tanaka et al ., 2019). Moreover, a shortened spawning season as in burbot [ Lota lota (L. 1758)] leads to a narrower temporal window for hatching (Ashton et al ., 2019).…”
Section: Elevated Temperature and Female Fish: From Oogenesis To Egg mentioning
confidence: 99%
See 1 more Smart Citation
“…These phenological shifts are particularly important as they dictate the biotic and abiotic conditions to which offspring will be exposed. Consequently, larval survival could be impacted due to mismatch with prey (plankton) abundance or proper size spectrum, for example due to delayed spawning time, inducing starvation or slower growth (Asch et al ., 2019; Farmer et al ., 2015; Hillebrand et al ., 2018; Tanaka et al ., 2019). Moreover, a shortened spawning season as in burbot [ Lota lota (L. 1758)] leads to a narrower temporal window for hatching (Ashton et al ., 2019).…”
Section: Elevated Temperature and Female Fish: From Oogenesis To Egg mentioning
confidence: 99%
“…Therefore, the comprehension of warming impacts on gametogenesis and their consequences on gamete quality is of great importance for aquaculture as well as reproductive ecology. However, while reproductive performance is a key attribute, it should be realized that populations might do poorly under climate change for other reasons, such as poleward displacement of important predators (Fossheim et al ., 2015), difficulties associated with long generation cycles (reduced possibility of adaptation), ecological specialization or overexploitation (Dulvy et al ., 2003; Hillebrand et al ., 2018), and temperature‐driven changes in reproductive timing and capacity will interact with these variables.…”
Section: Introductionmentioning
confidence: 99%
“…In the second half of the 21st century, the projected stabilization of biomass changes in the Arctic and Southern Ocean under RCP2.6 can be explained by changes in the forcing variables driven by strong climate change mitigation policies (van Vuuren et al, ), as indicated by the leveling off in projected SST and NPP trends (Supporting Information Figures S1 and S2). In contrast, under the high emissions scenario (RCP8.5), in which greenhouse gas emissions are projected to increase until 2100 (Riahi et al, ), the decline in projected total marine animal biomass in the Arctic may be attributed to continuing changes in the physical and biogeochemical environment, with consequences for the entire trophic network (Hillebrand et al, ). Indeed, longer term projections of changes in ocean ecosystems until 2300 suggest a strong decline in ocean productivity in the Northern Hemisphere and its shift toward the Southern Ocean (Moore et al, ; (Figure )).…”
Section: Discussionmentioning
confidence: 99%
“…For instance, new evidence suggests that red wolves (Canis rufus) that are currently protected under ESA are likely hybrids of gray wolves (C. lupus) and coyotes (C. latrans) (Waples, Kays, Fredrickson, Pacifici, & Mills, 2018;Wayne & Shaffer 2016). Second, incidents of hybridization have increased and will continue to increase in nature as climate change shifts species distributions and brings together previously isolated species and populations (Crispo et al, 2011;Garroway et al, 2010;Hillebrand et al, 2018;Moritz & Agudo 2013;Pauls, Nowak, Bálint, & Pfenninger, 2013;Pecl et al, 2017). Third, the lack of recognition of hybrids can be a lost opportunity to protect entities that can maintain vital ecosystem functions.…”
Section: Legal Framework That Impedes the Use Of Hybridization In Conmentioning
confidence: 99%